ANALYSIS OF VS30 AND PGA VALUES IN CENTRAL JAVA USING MIKROTREMOR DATA - Rahmi, Nur
Central Java is one of the area in Indonesia that has complex and active geological conditions. The existence of active volcanoes such as Mount Merapi, Mount Merbabu, Mount Ungaran, and the Dieng Plateau is evidence of the geological dynamics that occur in Central Java. In addition, there is the Kendeng Basin which is a continuation of the North Serayu Mountains that continues to the eastern part of Java. The study of the geological conditions in Central Java is a challenge, a seismological study is needed to complete the understanding of the subsurface structures. The Horizontal to Vertical Spectral Ratio (HVSR) method is important to extract dominant frequency values, amplification values, and shear wave velocity values which can be information to determine peak ground acceleration (PGA) values on the surface of the study area. This surface PGA value is important for soil mechanics analysis in geotechnical engineering. The data were from seismic records on the MERAMEX network and this study only utilized from 5 days of recorded data.. The HVSR curve profiles obtained were 81 clear peaks curves, 28 multiple peaks curves, and 11 types of two peaks. The dominant frequency values for the central part of Java range from 0.5 – 10.5 Hz, with low dominant frequency values classified as alluvial rocks with thick sediment and high dominant frequency values classified as areas with medium thickness tertiary rocks. The amplification value of this area is in the range of 0.7-13.6, with a low amplification value classified as an area with a low risk of damage due to earthquakes and a high amplification value classified as an area with a high risk of damage due to an earthquake. The value of the shear wave velocity at a depth of 30 meters found between 85-685 m/s, areas with low Vs30 values classified as SD sites or medium soils and areas with high Vs30 values classified as SC sites or hard soils. Peak ground acceleration values range from 0.26 – 0.77 g, with areas with low PGA values in the northern part of Central Java identified as having a relatively small earthquake risk while areas with high PGA value in the southern part of Central Java identified as having a high earthquake risk.